Theories of human development - Watson, Malcolm W.; Teaching Company (Chantilly, VA : The Teaching Company, 2002)
Professor Malcolm W. Watson of Brandeis University discusses various schools of thought in developmental psychology, including those of Freud, Erickson, Bandura, Ainsworth, Piaget, and Vygotsky
part I. lecture 1. Introduction - The value of theories ; lecture 2. The early history of child study ; lecture 3. Two worldviews - Locke vs. Rousseau ; lecture 4. Later history - Becoming scientific ; lecture 5. Freud's psychodynamic theory ; lecture 6. How we gain contact with reality - The ego ; lecture 7. Freud's psycho-sexual stages ; lecture 8. Erikson's psycho-social theory ; lecture 9. Erikson's early stage ; lecture 10. Identity and intimacy ; lecture 11. Erikson's later stages - Adult development ; lecture 12. Bowlby and Ainsworth's attachment theory -- part II. lecture 13. How nature ensures that attachment will occur ; lecture 14. Development of secure and insecure attachment ; lecture 15. Early attachments and adult relationships ; lecture 16. Bandura's social learning theory ; lecture 17. Bandura's self-efficacy theory ; lecture 18. Piaget's cognitive - Developmental theory ; lecture 19. Piaget's early stages ; lecture 20. Concrete operations ; lecture 21. Piaget's last stage ; lecture 22. Vygotsky's cognitive - Mediation theory ; lecture 23. Vygotsky's zone of proximal development ; lecture 24. Conclusions - Our nature and development
Title from title screen
Contains 24 lectures
Lecturer: Malcolm W. Watson
Keywords: Freud, Sigmund, -- 1856-1939; Erikson, Erik H. -- 1902-1994; Ainsworth, Mary D. Salter; Bandura, Albert, -- 1925-; Piaget, Jean, -- 1896-1980; Vygotskii, L. S. -- 1896-1934; Developmental psychology